Little women - Alcott, Louisa May; McFadden, Deanna; Mountford, Karl James (USSR Priory Books, 1989)
"Louisa May Alcott's novel, set during the Civil War, follows the adventures of the four March sisters-Meg, Beth, Amy, and, most of all, the tomboy Jo-as they experience the joys and disappointments, tragedies and triumphs, of growing up"--
740
M